Conjugation Of Foot And Mouth Disease IgY In Chicken Egg Yolk With Horse Radish Peroxidase For Typing Of Foot And Mouth Disease Virus - Ehab El-Sayed Ibrahim; Hamed Adel Hamed El-Helw; Nermen Guda Shafik; Manal Awad Mekhail (Journal of Applied Veterinary Sciences, 2017)
Through the present work, anti-FMD IgY immunoglobulins for serotypes O; A, and SAT2 were prepared in chicken egg yolk through immunization of laying hens with locally prepared trivalent FMD vaccine. The antibody titres against three serotypes (O; A, and SAT2) measured by SNT were 2.58; 2.8 and 2.6 respectively and where 2.81; 2.81 and 2.8 respectively when measured by ELISA. Evaluation of Anti-FMD IgY conjugated with Horse radish peroxidase for detection of FMD virus in 100 tongue epithelium; 50 OP fluid samples; 20 nasal swabs from naturally infected cattle, and 100 tissue culture infected fluids revealed sensitivity of 85% indicating the success of preparation of anti-FMD immunoglobulins conjugated with horse radish peroxidase as local product available on request saving cost and time.